2001
DOI: 10.1063/1.1413222
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microstructure on the carrier concentration of Mg-doped GaN films

Abstract: Room-temperature Hall effect measurements of (0001) Mg-doped GaN films grown on sapphire substrates by metalorganic chemical vapor deposition show a reduction in hole concentration for Mg concentrations greater than 1020 cm−3. A combination of secondary ion mass spectrometry and transmission electron microscopy indicates a steadily increasing Mg incorporation during growth and the formation of inversion domains at these high concentrations. We discuss mechanisms that could give rise to a reduction of the hole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 16 publications
2
53
2
1
Order By: Relevance
“…These results are well matched to the previous results, where the hole concentration initially increased with [Mg] and it decreased significantly with further increase in the [Mg]. [13] highest [Mg] and the lowest hole concentration, the current at 0.5 V was measured as 64 μA. It is worth to notice that the non-alloyed Pd/Pt/Au contacts deposited on samples A, B, and C displayed non-linear I-V curves, while I-V curve became linear for the contacts on sample D. This is suggestive of producing the better ohmic contact on sample D having the lowest hole concentration among the samples.…”
Section: Dependence Of Contact Resistivity On Hole Concentrationsupporting
confidence: 93%
“…These results are well matched to the previous results, where the hole concentration initially increased with [Mg] and it decreased significantly with further increase in the [Mg]. [13] highest [Mg] and the lowest hole concentration, the current at 0.5 V was measured as 64 μA. It is worth to notice that the non-alloyed Pd/Pt/Au contacts deposited on samples A, B, and C displayed non-linear I-V curves, while I-V curve became linear for the contacts on sample D. This is suggestive of producing the better ohmic contact on sample D having the lowest hole concentration among the samples.…”
Section: Dependence Of Contact Resistivity On Hole Concentrationsupporting
confidence: 93%
“…Chang and co-workers 6 detected Mg accumulation by AES on the surface of GaN with bulk Mg density of 2Ϫ3ϫ10 19 cm Ϫ3 ͑determined by SIMS͒. Romano and co-workers 12 and oxygen concentrations increased near the surface region of Mg-doped GaN. Nakano and Jimbo 13 recently pointed out outdiffusion of Mg to the surface during activation annealing above 800°C.…”
Section: Resultsmentioning
confidence: 99%
“…vs. V "Mott-Schottky" plots) is indicative of the net charge type (donor or acceptor) beneath the surface inversion/accumulation layer [10,11]. This "turnover" occurs at lower applied bias shown to produce donors and reduce the free hole concentration; this result has been attributed to the formation of compensating defect complexes (such as Mg-V N ) [32,33] and pyramidal inversion domains [34,35]. TEM studies of Mg-doped InN, InGaN, and GaN have shown that high levels of Mg result in large densities of planar extended defects, which could also be contributing to the n-type conductivity of overdoped films [36][37][38][39].…”
Section: Electrical and Thermoelectric Measurements A Resultsmentioning
confidence: 99%